Algorithm and Language - Marconatto, Arildo (Universidad de Costa Rica, 2020)
The aim of this paper is to highlight characteristic elements of the relationship between algorithmic data processing and human language. We also seek to analyze the interactions of human language with the evolution of algorithms and their uses. We conclude that human language is progressively influenced as the goals to be achieved by the algorithms progress and evolve.